Molecular Mechanisms Underlying Hepatocellular Carcinoma Induction by Aberrant NRF2 Activation-Mediated Transcription Networks: Interaction of NRF2-KEAP1 Controls the Fate of Hepatocarcinogenesis - Haque, Effi; Karim, M Rezaul; Salam Teeli, Aamir; Śmiech, Magdalena; Leszczynski, Paweł; Winiarczyk, Dawid; Parvanov, Emil D; Atanasov, Atanas G; Taniguchi, Hiroaki (International journal of molecular sciences, 2020)
NF-E2-related factor 2 (NRF2) is a basic leucine zipper transcription factor, a master regulator of redox homeostasis regulating a variety of genes for antioxidant and detoxification enzymes. NRF2 was, therefore, initially thought to protect the liver from oxidative stress. Recent studies, however, have revealed that mutations in NRF2 cause aberrant accumulation of NRF2 in the nucleus and exert the upregulation of NRF2 target genes. Moreover, among all molecular changes in hepatocellular carcinoma (HCC), NRF2 activation has been revealed as a more prominent pathway contributing to the progression of precancerous lesions to malignancy. Nevertheless, how its activation leads to poor prognosis in HCC patients remains unclear. In this review, we provide an overview of how aberrant activation of NRF2 triggers HCC development. We also summarize the emerging roles of other NRF family members in liver cancer development.
Keywords: aktivace transkripce; Gene Expression Regulation, Neoplastic; analýza přežití; oxidační stres; mutace; faktor 2 související s NF-E2; Cell Line, Tumor; NF-E2-Related Factor 2; prognóza; Gene Regulatory Networks; regulace genové exprese u nádorů; signální transdukce; Carcinoma, Hepatocellular; Transcriptional Activation; Signal Transduction; KEAP-1; Survival Analysis; oxidace-redukce; genové regulační sítě; Carcinogenesis; lidé; Humans; Kelch-Like ECH-Associated Protein 1; karcinogeneze; hepatocelulární karcinom; Prognosis; Mutation; nádorové buněčné linie; Liver Neoplasms; Oxidation-Reduction; Oxidative Stress; nádory jater